2014
DOI: 10.14260/jemds/2014/2487
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Resis Tance Pattern of Acinetobacter Species in Hospitalized Patient S in a Tertiary Care Centre

Abstract: BACKGROUND: Acinetobacter species are one of the most frequent nosocomial pathogen causing bacteremia, urinary tract infection, secondary meningitis, skin and soft tissue infections and in particular nosocomial pneumonia with high mortality rate. The infections due to these are often difficult to treat due to their high antibiotic resistance. AIMS: To Study the prevalence and resistance pattern of Acinetobacter species in hospitalized patients of Era's Lucknow Medical College and Hospital (ELMCH), Lucknow. MAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
7
3
1
Order By: Relevance
“…The highest number of isolates were recovered from tracheal aspirates, pus and urine samples, consistent with results from studies in several hospitals in India [17, 22] and Morocco [9]. These results were in contrast with those reported in two separate studies done in India [23, 24] which showed highest number of isolates were from tracheal aspirate followed by blood and pus respectively. The rate of isolation from different clinical samples is mostly influenced by the differences in the sample types, antibiotic usage, previous history of specific site colonization, infection control practices and a times the type of health facility.…”
Section: Discussionsupporting
confidence: 87%
“…The highest number of isolates were recovered from tracheal aspirates, pus and urine samples, consistent with results from studies in several hospitals in India [17, 22] and Morocco [9]. These results were in contrast with those reported in two separate studies done in India [23, 24] which showed highest number of isolates were from tracheal aspirate followed by blood and pus respectively. The rate of isolation from different clinical samples is mostly influenced by the differences in the sample types, antibiotic usage, previous history of specific site colonization, infection control practices and a times the type of health facility.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the highest number of isolates was obtained from ICU; A. baumannii was mostly found in trachea samples. Almost similar results were observed in a study by Sana Islahi in India (23). Most of the strains were highly resistant to the antibiotics.…”
Section: Discussionsupporting
confidence: 87%
“…The clinical impact of the Acinetobacter was increasing morbidity or mortality, and their infections are responsible for the rise inpatient mortality that happens in critically unwell patients, it's thought-about as a low virulence organism except when isolated in critically ill or immunocompromised patients. These organisms are most frequently related to nosocomially instead of community-acquired infections, which agrees with a previous study (Jain and Danziger, 2004) (Doughari et al, 2010) (Islahi et al, 2014). A. baumannii's ability to develop multi-drug resistance and trigger harsh environmental conditions make Acinetobacter infection very serious, especially in individuals who have recently undergone surgery or have diseases, malignant burns or immunocompromised patients such as the elderly and newborns.…”
Section: Resultssupporting
confidence: 89%